Analisis Peluang Dan Tantangan Perdagangan Internasional Produk Perkebunan Kelapa Sawit Indonesia – India - Dila Nur Kharisma (Jurnal Ekonomi dan Bisnis Digital, 2026)
Indonesia is one of the world’s leading palm oil producers, with India as a major export destination due to its high demand for vegetable oil. This study aims to analyze the opportunities and challenges of palm oil trade between Indonesia and India in 2025 using qualitative and quantitative approaches. The results show opportunities from high demand in India, Indonesia’s production advantage, and strong bilateral relations, supported by relatively stable export trends. However, challenges include global price fluctuations, India’s import policies, environmental issues, and international competition. Therefore, appropriate strategies are needed to maintain Indonesia’s competitiveness in the global market.